2011
DOI: 10.1007/s00408-011-9280-9
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus Lung Disease in Patients with Sarcoidosis: A Case Series and Review of the Literature

Abstract: Chronic cavitary pulmonary aspergillosis (CCPA) has been associated with advanced lung diseases. Pulmonary sarcoidosis, a granulomatous inflammatory disorder, is associated with CCPA. We identified CCPA in 2% of cases in a large cohort of sarcoidosis patients. We found a lack of response to medical treatment and poor outcome in this subgroup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 34 publications
1
50
0
1
Order By: Relevance
“…In US studies up to 1984, cavitation rates varied from 2% to 12.5% and aspergilloma rates from 1% to 11% [29][30][31][32][33][34][35][36]. In later studies from Israel, Turkey and France, aspergilloma rates varied from 0% to 2.1% [1,37,38].…”
Section: Cpa Complicating Sarcoidosismentioning
confidence: 99%
See 1 more Smart Citation
“…In US studies up to 1984, cavitation rates varied from 2% to 12.5% and aspergilloma rates from 1% to 11% [29][30][31][32][33][34][35][36]. In later studies from Israel, Turkey and France, aspergilloma rates varied from 0% to 2.1% [1,37,38].…”
Section: Cpa Complicating Sarcoidosismentioning
confidence: 99%
“…In 18 patients, an aspergilloma was present on initial computed tomography scan and, in three more, one developed during follow-up, a 51% rate in those with cavitation and a 2% rate overall. In the USA, PENA et al [36] found 10 patients with an aspergilloma among 427 (2.3%) patients with pulmonary sarcoidosis. Neither study utilised Aspergillus serology, unlike WOLLSCHLAGER and KHAN [29] in 1984.…”
Section: Cpa Complicating Sarcoidosismentioning
confidence: 99%
“…Although fungus balls can be caused by many fungi, most are caused by members of the Aspergillus genus [70,72]. The exact incidence of aspergillomas in sarcoidosis is uncertain, although studies report an incidence of ,2% [70,73].…”
Section: Parenchymal Complications Cavities and Mycetomasmentioning
confidence: 99%
“…Haemoptysis has been ascribed to local vascular invasion of the cavity wall by Aspergillus organisms. Collateral vessels from the bronchial arteries and from systemic arteries of the chest wall may augment the blood supply to inflammatory tissue around the cavity, predisposing to serious bleeding [70][71][72][73]76]. Other potential pathogenic mechanisms have been proposed, including friction of the mobile fungus ball against a hypervascular wall, toxins or enzymes released by the fungus, a type III antibody-antigen reaction, and conversion to chronic necrotising aspergillosis.…”
Section: Parenchymal Complications Cavities and Mycetomasmentioning
confidence: 99%
See 1 more Smart Citation